A Low-Voltage High PSRR and High Precision CMOS Bandgap Reference - Zhou Qianneng; Xue Rong; Li Hongjuan; Lin Jinzhao; Li Qi; Pang Yu; Li Guoquan (Institute of Advanced Engineering and Science, 2014)
By adopting the technique of pre-regulator, a high PSRR and low temperature coefficient piecewise-linear bandgap reference (BGR) is designed for analog and mixed-signal application in this paper. The piecewise-linear BGR with pre-regulator, which is analyzed and simulated in SMIC 0.18μm CMOS process, has simple circuit architecture. Simulation results show that piecewise-linear BGR with pre-regulator achieves power supply rejection ratio (PSRR) of -102.488dB and -99.73dB, -82.983dB at 10Hz, 100Hz and 1kHz respectively. Piecewise-linear BGR with pre-regulator achieves the temperature coefficient of 2.235 ppm/°C when temperature is in the range from -50°C to 115°C. When power supply voltage VDD changing from 1.2V to 10V, output voltage deviation of piecewise-linear BGR with pre-regulator is only 0.2765mV, but output voltage of piecewise-linear BGR without pre-regulator has a deviation of 38.08mV. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4056